Microfluidics and Macrofluidics in Space: ISS-Proven Fluidic Transport and Handling Concepts - Nijhuis, Job; Schmidt, Svenja; Tran, Nam Nghiep; Hessel, Volker (Frontiers in Space Technologies, 2022)
Fluid transport and handling in extraterrestrial conditions, i.e. microgravity, require significantly different system engineering than here on Earth. On Earth, a notable part of fluid processing units inherently relies on buoyancy to transport and handle fluids. In space, however, buoyancy effects are negligible due to the strong diminishment of gravity, resulting in the domination of surface tension forces. Surface tension forces are also dominating micro-scale processes in gravity, making microfluidics a promising technology for fluidic transport and handling in microgravity. Recently, three different microfluidics-suitable fluid behavior phenomena have been studied on the ISS that might further facilitate the manipulation of fluids in space: capillary-driven flow, thermocapillary Marangoni forces, and electrolytic gas evolution-driven flow. Furthermore, attention is drawn for strategies to eliminate unwanted bubbles from liquid bodies in space, as they can damage sensitive equipment: Mesh-screen capillarity and open wedge channels have been identified as promising approaches. Finally, the relevance of fluid handling in space is illustrated with everyday activities during space missions, such as drinking, plant watering, and gathering biometric data.